Material Geographies of Household Sustainability. - Lane, Ruth (Ashgate Pub., 2011)
Social and cultural change at the household level is critical to promoting sustainability at a range of wider scales. This book constructs a series of imperatives for linking culturally informed research around household sustainability with policy and planning.